Impacts of Different Mulch Type on Growth, Yield, and Quality of Tomato (Solanum lycopersicum L.): A Review - Faizi, Zabihullah; Salari, Hamid; Zamany, Ahmad Jawid; Amin, Mohammadullah; Ziarmal, Nasir Ahmad (Journal of Natural Sciences – Kabul University, 2025)
Different types of mulches, such as organic mulch, plastic mulch, and biodegradable mulches, have a significant effect on tomato growth, yield, quality, and soil properties. Mulch also helps maintain soil moisture, regulate temperature, and control weeds. Black plastic mulch often results in higher tomato yield, while organic and biodegradable mulches can serve as a sustainable alternative to plastic mulch for environmental protection. Economically, plastic mulch provides short-term high yields, whereas organic and biodegradable mulches are cost-effective and easily available, leaving no residues. The effectiveness of mulch depends on its type, color, thickness, irrigation, fertilization, and other agronomic practices. Therefore, farmers are advised to use mulch to achieve high, quality, and economical tomato yield.